Effect of Breast Cancer Detection Application on Improving Knowledge of Early Detection of Breast Cancer (BSE) among Adolescents - Erika; Didi Kurniawan; Aprianti, Siska (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Breast cancer is one of the most common cancers women suffer, especially in adolescents and young adults. Objective: This study aims to determine the effect of the application of early detection of breast cancer to increase knowledge about early detection of breast cancer in adolescents. Method: This study used a pre-experimental design with a one-group pre-test post-test design approach. The study sample amounted to 100 respondents with sampling using a purposive sampling technique. The analysis used was bivariate and gene analysis using Wilcoxon. Result: The characteristics of the majority of respondents are middle-aged adolescents 15 to 17 years (91%), have never received education about breast cancer and how to prevent it (73%), and the level of knowledge about breast cancer is sufficient (54). The Wilcoxon alternative test results compared the knowledge level before, and after using an Android-based breast cancer early detection application obtained p value = 0.000 < (0.05). Conclusion: In conclusion, this study has an effect of early detection of breast cancer in increasing knowledge about the early detection of breast cancer in adolescents. Recommendation: The results of this study are expected to increase knowledge about breast health education through an Android-based early detection application for breast cancer in adolescents that can apply to the implementation of nursing. Researchers suggest that future researchers can use creativity so that this research can attract more respondents' attention and be able to increase the knowledge of adolescents